Evaluation of the relationship between residential orchard density and dimethyl organophosphate pesticide residues in house dust - Plascak, Jesse J. (J Expo Sci Environ Epidemiol, 2019)
Reducing residential pesticide exposure requires identification of exposure pathways. mCompared to the agriculture worker ‘take-home’ and residential use pathways, evidence of the ‘drift’ pathway to pesticide exposure has been inconsistent. Questionnaire data from individuals (n=99) and dust samples (n=418) from households across three growing seasons in 2011 were from the For Healthy Kids! study. Summed dimethyl organophosphate pesticide (OP) (Azinphos-Methyl, Phosmet, and Malathion) concentrations were quantified from house dust samples. Spatially-weighted orchard densities surrounding households were calculated based on various distances from homes. Regression models tested associations between orchard density, residential pesticide use, agriculture worker residents, and summed dimethyl OP house dust concentrations. Estimated relationships between orchard density and dimethyl OP in house dust were mixed: a 5% increase in orchard density resulted in 0.3% and 0.5% decreases in dimethyl OP house dust concentrations when considering land-cover 750m or 1250m away from households, respectively, but null associations with land-cover 60m or 200m away. Dimethyl OP house dust concentrations were 400% higher within homes where at least two residents were agriculture workers. Despite inconclusive evidence for the drift pathway due to potential for bias, relationships between number of agriculture workers and dimethyl OP house dust concentration underscores the take-home pathway.